Euphemism in Translation of Al-Qur’an Bacaan Mulia by H.B. Jassin - Jauhari, Falah; Baehaqie, Imam (Universitas Jambi, Magister Program of English Education Department, 2026)
This study aims to describe the forms of euphemism found in Al-Qur’an Bacaan Mulia, an Indonesian translation of the Qur’an by H.B. Jassin, particularly in verses related to gender issues. This research employed a descriptive qualitative approach grounded in the theories of euphemism proposed by Allan and Burridge as well as Olimat’s euphemism analysis model. The data consisted of words, phrases, and sentences containing euphemistic expressions in verses concerning male–female relations, marital relations, aurat, divorce, inheritance, and other gender-related issues. Data were collected through observation, documentation, and note-taking techniques. The data were analyzed using distributional and identity methods through direct element division and comparative techniques. The findings reveal five forms of euphemism in Al-Qur’an Bacaan Mulia: substitution, circumlocution, generalization, remodelling, and metaphor. These euphemistic forms are used to soften expressions related to sexuality, gender relations, and body parts considered sensitive. The use of euphemism in Jassin’s translation demonstrates the integration of Qur’anic meaning with literary aesthetics and linguistic politeness. Furthermore, the study indicates that diction choices in Qur’anic translation may influence readers’ understanding of gender meanings within the sacred text.